Evaluating the effect of life cycle cost forecasting accuracy on mining project valuations - Van Vuuren, Stefanus Hendrik Jansen (My University, 2013)
The study was conducted to establish what effect life cycle cost forecasting accuracy has on project valuations with special reference to a global mining organisation’s coal business unit in South Africa. The research stemmed from the fact that the organisation identified through its own research in 2009 that its capital projects rarely met the originally budgeted life cycle cost forecasts estimated during the project development stages. These forecasts were generally found to be underestimated. Overrunning of cost budgets in project management terms results in project failure. The study employed two main empirical research sections. The first section took a case study approach where past implemented project results were collated and analysed. The main aim was to determine how close to reality the original life cycle cost estimates were, and secondly how any variances to the originally budgeted costs impacted on the anticipated project value post implementation. Secondly, the study employed in-depth interviews with seven project specialists within the organisation that were also involved in the development stages of the investigated projects. The study concluded that life cycle cost forecasts are very important project business case inputs and that the necessary time and effort should go into developing them so as to ensure that they are as comprehensive and accurate as possible. The sensitivity analysis that was conducted revealed that a coal mining project business case is the second most sensitive to variations in life cycle costs after variations in commodity price. The results indicated that a 20% increase in life cycle costs can destroy an equivalent project value of up to 100%. Accurate life cycle cost forecasting is therefore essential in order to estimate to a certain degree of accuracy the value of a project which in turn will be used to inform capital investment decision making.
MBA, North-West University, Potchefstroom Campus, 2014
Keywords: Life Cycle Costs; Forecasting Accuracy; Capital Project Development; Project Valuation; Life Cycle Costing (LCC)